Simultaneous pO2 and HbO2 measurement to determine absolute HbO2 concentration for in vivo near infrared spectroscopy. Issue 2 (2003) - Macnab Macnab, Andrew J. Andrew J.; Gagnon Gagnon, Roy Roy; Gagnon Gagnon, Faith Faith; Minchinton Minchinton, Andrew I. Andrew I.; Fryer Fryer, Karen H. Karen H.
Abstract : Purpose : Near infrared spectroscopy (NIRS) monitors absolute changes in concentration of chromophores from an unquantified baseline. A change in oxygenation is required to obtain information. Clinically, knowing initial chromophore concentration is desirable. We sought absolute initial concentrations by combining NIRS measurements with simultaneous Eppendorf histograph measurement (absolute values of tissue partial pressure of oxygen (pO2 )). Methods : There were 22 trials on 9 occasions in 2 adult volunteers. Following local anaesthetic, the histograph probe was inserted into the forearm muscle and NIRS optodes applied. A sphygmomanometer cuff was inflated over the upper arm to produce ischaemia and hypoxia. Change in pO2 was determined as a percentage of the initial pO2 . Change in HbO2 was measured, and the initial HbO2 calculated by assuming the percentage change in HbO2 equaled the percentage change in pO2 . Results : Mean percentage change in pO2 was 20.7 ± 9.6. Mean change in HbO2 was 22.4 ± 3.4 µ mol/l(tissue). Calculated initial HbO2 was 146.4 ± 108.7 µ mol/l(tissue), range 51 to 508 µ mol/l(tissue). Correlation ( r 2 ) between pO2 and HbO2 was 0.97 ± 0.03. Conclusion : Although changes in pO2 and HbO2 were highly correlated, calculation of initial absolute concentration of HbO2 was not achieved by this method. A reliable method of obtaining absolute concentrations of HbO2 in vivo remains to be found.